Moisture‐Assisted Preparation of Compact GaN:ZnO Photoanode Toward Efficient Photoelectrochemical Water Oxidation. Issue 20 (19th July 2016) - Wang, Zhiliang; Han, Jingfeng; Li, Zheng; Li, Mingrun; Wang, Hong; Zong, Xu; Li, Can
Abstract : Developing strategies that can promote charge transportation in photodevices is crucial for achieving high solar energy conversion efficiency. Herein a moisture‐assisted nitridation approach is presented for the fabrication of efficient gallium‐zinc oxynitride (GaN:ZnO) photoanode with compact structure to facilitate the charge transportation. With moisture‐assisted nitridation, the charge separation efficiency and injection efficiency obtained on GaN:ZnO photoanode are significantly enhanced. Correspondingly, the photocurrent at 1.23 V vs reversible hydrogen electrode (RHE) has 18 folds improvement compared with that prepared without moisture assistance. Furthermore, via treating with HCl acid and modification with cobalt phosphate (CoPi) as a cocatalyst, state‐of‐the‐art photocurrent over 2.0 mA cm −2 is achieved on independent GaN:ZnO photoanode when bias is higher than 1.4 V vs RHE. To the best of our knowledge, this is the first paradigm of moisture‐assisted preparing oxynitride‐based photoanode. The participation of moisture is found to improve the interconnection between adjacent GaN:ZnO nanoparticles as well as that between the GaN:ZnO film and the underlying substrate. Moreover, the volatilization of Zn can be substantially suppressed due to the modulation of reaction pathway by moisture. These two factors are confirmed to be the main reasons for the enhanced charge transportation and PEC performance obtained on GaN:ZnO photoanode. Abstract : With the assistance of moisture during nitridation, compact GaN:ZnO photoanode with high Zn content can be prepared. It shows improved charge transportation and injection for photoelectrochemical water oxidation, and thus much higher photocurrent than the electrode prepared without moisture. And the highest photocurrent of GaN:ZnO photoanode can be achieved by further treating with HCl acid and modifying with cobalt phosphate.